Influence of skin contact and different extractants on extraction of proteins and phenolic substances in Sauvignon Blanc grape skin. (10th March 2020) - Tian, B.; Harrison, R.; Morton, J.; Jaspers, M.
Abstract: Background and Aims: Although most proteins and a significant proportion of phenolic substances are extracted from grape pulp, the extraction of grape skin components may contribute to and modulate the final concentration of these components in juice. This study investigated the influence of skin contact time and various extractants on the extraction of Sauvignon Blanc grape skin components. Methods and Results: Two trials were conducted. The first evaluated the impact of skin contact time on the extraction of phenolic substances and proteins from grapes (fresh vs chilled) into juice. The juice with 24 h skin contact showed a significantly higher concentration of phenolic substances and chitinases, but not of thaumatin‐like proteins. No difference was observed between fresh and chilled berries. The second trial evaluated the extractability of phenolic substances and proteins from grape skin (ground vs peeled) using different extractants. More phenolic substances and tannin were extracted using ground skin powder as greater mechanical damage assisted in the extraction of skin components. Compared to mechanically crushed and pressed grape juice, hand squeezed juice showed a lower protein concentration and the presence of tannin. It is suggested that hand squeezing was more effective in extracting components (mainly phenolic substances) from grape skin, but mechanically crushing and pressing was more effective in extracting components (mainly proteins) from grape pulp. Extractants containing bovine serum albumin or protein resulted in a lower concentration of phenolic substances and tannin in the extracts, and the concentration of bovine serum albumin and protein was dramatically decreased after extraction. Conclusion: This study confirmed that longer skin contact increased the extraction of skin phenolic substances. Longer skin contact also increased the protein concentration in juice, particularly the pathogenesis‐related proteins, but it can be modulated by the co‐extraction of phenolic substances. Significance of the Study: This study improves our current understanding of interactions between phenolics and proteins during grape processing, which can be used as a tool for winemakers to manage the extraction of these compounds into juice.